Detection of cannabinoid receptor type 2 in native cells and zebrafish with a highly potent, cell-permeable fluorescent probe. Issue 19 (22nd April 2022) - Gazzi, Thais; Brennecke, Benjamin; Atz, Kenneth; Korn, Claudia; Sykes, David; Forn-Cuni, Gabriel; Pfaff, Patrick; Sarott, Roman C.; Westphal, Matthias V.; Mostinski, Yelena; Mach, Leonard; Wasinska-Kalwa, Malgorzata; et al.
Abstract : Detection and visualization of the cannabinoid receptor type 2 by a cell-permeable high affinity fluorescent probe platform enables tracing receptor trafficking in live cells and in zebrafish. Abstract : Despite its essential role in the (patho)physiology of several diseases, CB2 R tissue expression profiles and signaling mechanisms are not yet fully understood. We report the development of a highly potent, fluorescent CB2 R agonist probe employing structure-based reverse design. It commences with a highly potent, preclinically validated ligand, which is conjugated to a silicon-rhodamine fluorophore, enabling cell permeability. The probe is the first to preserve interspecies affinity and selectivity for both mouse and human CB2 R. Extensive cross-validation (FACS, TR-FRET and confocal microscopy) set the stage for CB2 R detection in endogenously expressing living cells along with zebrafish larvae. Together, these findings will benefit clinical translatability of CB2 R based drugs.